Bailouts and financial fragility - Todd Keister (Rutgers University, Department of Economics, 2014)
Should policy makers be prevented from bailing out investors in the event of a crisis? I study this question in a model of financial intermediation with limited commitment. When a crisis occurs, the policy maker will respond by using public resources to augment the private consumption of those investors facing losses. The anticipation of such a "bailout" distorts ex ante incentives, leading intermediaries to choose arrangements with excessive illiquidity and thereby increasing financial fragility. Prohibiting bailouts is not necessarily desirable, however: while it induces intermediaries to become more liquid, it may nevertheless lower welfare and leave the economy more susceptible to a crisis. A policy of taxing short-term liabilities, in contrast, can both improve the allocation of resources and promote financial stability.
Keywords: G28; 330; bank runs; bailouts; moral hazard; financial regulation